ANALISIS VALIDITAS, RELIABILITAS, INDEKS KESUKARAN DAN DAYA PEMBEDA INSTRUMEN TES KEMAMPUAN NUMERASI BERBASIS ETNOMATEMATIKA - Yumira Mira Simamora; Minta Ito Simamora (Universitas Islam Sumatera Utara, 2025)
This research is part of an experimental study using Problem Based Learning model to improve junior high school students' mathematical numeracy skills based on ethnomathematics. The purpose of this study is to determine the level of Validity, Reliability, Difficulty Index, and Discriminatory Power of the ethnomathematics-based numeracy ability test instrument for junior high school students. The instrument used was in the form of essay test questions from pretest and posttest questions. The calculation of validity, reliability, difficulty index, and discriminatory power used IBM SPSS Statistics 20. The results of this study showed that the pretest and posttest questions were valid with sig (2-tailed) values 0.05. The calculation results of the pretest questions showed that the essay question instrument fell into the reliable category, because the calculation result obtained was 0.690, making it suitable for use as an instrument for data collection. The difficulty level of pretest and posttest questions fell into the easy and moderate categories. The discriminatory power criteria of the questions were moderate and good. Based on these research results, the ethnomathematics-based student numeracy ability test instrument is suitable for use.